KENDALA DAN SOLUSI IMPLEMENTASI SUBSIDI BENIH PADI DI PROVINSI SUMATERA SELATAN - Valeriana Darwis (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2017)
Abstract : Seed is one of the main elements in rice cultivation. Use of seed labeled andquality will have a positive impact on productivity. This strategic role of seed which isthe reason the government helps farmers by conducting seed subsidies. Subsidizationof seed carried out throughout Indonesia and one of them is the province of SouthSumatra. The objective is to see the implementation of subsidized seeds with the mainfocus of the implementation challenges and solutions such activities. By 2016 subsidysurvay seed at the time of implementation was not up to 10 percent. The main cause ofthis low uptake by PSO is a delay DUPBB that the main basis of PSO prepares andprovides rice seeds. Despite the low uptake but seed subsidies still need to be passedon, this is due to the use of seed labeled and quality in South Sumatra Province is stilllow, and to overcome implementation seed subsidies in the future need to be increaseddissemination activities, the introduction of new varieties of R & D, the certainty ofthe selection of varieties, increasing the number of seeds subsidized and incentives forenumerators DUPBB.Abstrak : Benih merupakan salah satu unsur utama dalam budidaya padi. Pemakaianbenih berlabel dan bermutu akan memberikan dampak positif pada produktivitas.Peranan benih yang strategis ini merupakan alasan pemerintah membantu petanidengan melaksanakan kegiatan subsidi benih. Pemberian subsidi benih dilakukandiseluruh Indonesia dan salah satunya adalah Provinsi Sumatera Selatan. Tujuanpenulisan ini adalah melihat pelaksanaan subsidi benih dengan fokus utama kendaladan solusi implementasi dari kegiatan tersebut. Pada tahun 2016 subsidi benih padasaat dilakukan survay pelaksanaannya tidak sampai 10 persen. Penyebab utamaserapan rendah ini menurut PSO adalah keterlambatan DUPBB yang menjadi dasarutama PSO menyiapkan dan memberikan benih padi. Meskipun rendah serapan tetapisubsidi benih masih perlu diteruskan, hal ini disebabkan pemakaian benih berlabel danbermutu di Provinsi Sumatera Selatan masih rendah, Dan untuk mengatasi kendalaimplementasi subsidi benih kedepannya perlu ditingkatkan sosialisasi kegiatan,pengenalan varietas baru litbang, kepastian pemilihan varietas, penambahan jumlahbenih yang disubsidi dan pemberian insentif bagi petugas pendata DUPBB.